Erosion and loss of nutrients in different farming systems of a watershed in the periurban area of the city of Puebla, Mexico. - Castelán Vega, Rosalía del Carmen; López Teloxa, Leticia Citlaly; Tamariz Flores, José Víctor; Linares Fleites, Gladys; Cruz Montalvo, Abel (REVISTA TERRA LATINOAMERICANA, 2017)
Soil is a natural component of great importance to ecosystem sustainability. Degradation of hillside soil conditions is due, in most cases, to poor management, which diminishes soil productivity and its ability to sustain human life. Production of sediment and nutrient loss during 2013 was evaluated in agricultural systems representative of the periurban zone of the city of Puebla, Mexico, to weight the enrichment coefficient of these sediments, and thus identify the agricultural system that generates less fertility loss. Delimited plots 3 m wide and 9 m long with a homogeneous slope of 9% were installed in maize, maize-squash and maize-oats crop systems. The sediments were collected, and concentrations of organic matter, nitrogen and phosphorus were determined, as marked by NOM-021-SEMARNAT-2000. Sediment yield and runoff were significantly higher in maize (54.6 mm and 37.9 Mg ha‑1, respectively) and lower in maize-squash plots. The enrichment coefficients of the eroded sediments were mostly higher than one, and organic matter had the highest coefficients. There was a strong correlation between sediment production and losses of organic matter, nitrogen and phosphorus in agricultural systems. The results obtained demonstrate that the current management of agricultural crops in the study area favors soil degradation. Likewise, the results generated are an important basis for establishing agricultural strategies and reducing degraded areas of the rural periurban area of the city of Puebla, Mexico.